Sistema de Ejercicios para Mejorar la Coordinación en Niños de 7 a 9 Años en la Escuela de Educación Básica "Isabel Católica" - AREVALO MONTOYA KELVIN JOSE (2024)
The Exercise System to improve coordination in children from 7 to 9 years old, addresses the worrying lack of development of motor coordination in children of that age. The problem is contextualized within the framework of the importance of physical education for the health and well-being of children at a global level, and the need for early intervention at the "Isabel Católica" Basic Education School is identified. The justification is based on the relationship between motor coordination and the general wellbeing of children, as well as the lack of structured programs to address this deficiency. The design, implementation and evaluation of an Exercise System adapted to the specific needs of the children of that school is proposed, with the objective of optimizing their integral development and encouraging their active participation in physical, social and academic activities. The research is supported by antecedents that highlight the importance of motor development in childhood and by theoretical bases that support the proposed intervention. The results of the survey show a high level of acceptance and satisfaction by the participating children with the Exercise System, which indicates its effectiveness in improving coordination and its positive impact on the children's general well-being. It is recommended to adapt the program according to individual needs, establish interdisciplinary collaborations, integrate educational technology, implement active participation strategies, and provide continuous training to physical educators and teachers.